1999
DOI: 10.1016/s0378-7753(99)00111-1
|View full text |Cite
|
Sign up to set email alerts
|

Copper–tin anodes for rechargeable lithium batteries: an example of the matrix effect in an intermetallic system

Abstract: The submitted manuscript has been created by the University of Chicago as Operator of Argonne National Laboratory~Argonne") under Contract No. W-31-109-ENG-38 with the U.S. Department of Energy. The U.S. Government retains for itself, and others acting on its behalf, a paid-up, nonexclusive, irrevocable worldwide license in said article to reproduce, prepare derivative works, distribute copies to the public, and perform publicly and display publicly, by or on behalf of the Government.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
127
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(132 citation statements)
references
References 8 publications
4
127
0
1
Order By: Relevance
“…Among them, tin seems to be particularly attractive since it easily and reversibly alloys with Li atoms at potentials <1.1 V vs. Li. Other attractive properties of tin include fast Li diffusion, better safety, easy mechanical processing, and crucially, a high gravimetric 993 mAhg -1 and volumetric 7262 mAhcm -3 specific theoretical capacities [18,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Among them, tin seems to be particularly attractive since it easily and reversibly alloys with Li atoms at potentials <1.1 V vs. Li. Other attractive properties of tin include fast Li diffusion, better safety, easy mechanical processing, and crucially, a high gravimetric 993 mAhg -1 and volumetric 7262 mAhcm -3 specific theoretical capacities [18,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…For this investigation, the Cu 6 Sn 5 alloy in the Cu-Sn system was chosen for the following reasons: 1) It has been shown that as Li is added to Cu 6 Sn 5 , it eventually decomposes to a Li-Sn alloy (active) surrounded by a Cu matrix (inactive) (i.e., forms active-inactive composite) [11][12][13][14]; 2) The volumetric capacity of a Cu 6 Sn 5 alloy made by conventional melting [12] at 10 cycles was about twice the capacity for graphite, whereas for the Cu 6 Sn 5 alloy at 25 cycles made by mechanical alloying [14], the capacity was about three times that for graphite. Thus, Cu 6 Sn 5 has potential as a replacement for graphite in Li-ion batteries if its cycle life can improved; and 3) there is experimental evidence for the Cu 6 Sn 5 alloy in the micron-size particle range that as the particle size is decreased, an improvement in cycle life is exhibited [15].…”
Section: Materials Selectionmentioning
confidence: 99%
“…Recently, there has been interest in the use of composites consisting of a lithium active metal (metal that alloys with lithium (Li), i.e., tin (Sn)) dispersed within an inactive matrix (i.e., copper (Cu)) as replacement anodes for graphite in Li-ion batteries [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. Active-inactive composites are preferred over an anode consisting only of a lithium alloy, even though there is loss of specific capacity because of the extra weight of the inactive component because the cycle life of the alloy is very limited.…”
Section: Contents Introductionmentioning
confidence: 99%
“…Many alloy systems are being developed to replace graphite as the anode in lithium rechargeable batteries due to their better capacity (Sn-Cu, [1][2][3][4] Li-Sn, 5) Cu-Sb, 6) Mg-Si 7) and Li-Si 8) ). Sn-based intermetallic compounds and their oxides 9,10) possess higher capacity, and numerous relevant reports have investigated Sn-Cu, [1][2][3][4] Sn-Mo, 11) Sn-P, 12) Sn-Ni, [13][14][15] Sn-Ca, 16) Sn-Sb, 17) Sn-S, 18) Li-Sn, 5) Ce-Sn, 7) and Sn-O.…”
Section: Introductionmentioning
confidence: 99%
“…Sn-based intermetallic compounds and their oxides 9,10) possess higher capacity, and numerous relevant reports have investigated Sn-Cu, [1][2][3][4] Sn-Mo, 11) Sn-P, 12) Sn-Ni, [13][14][15] Sn-Ca, 16) Sn-Sb, 17) Sn-S, 18) Li-Sn, 5) Ce-Sn, 7) and Sn-O. 9,10) Notably, most of the above Sn-based anode materials were prepared by mechanical alloying (ball milling), 4,13,19,20) sintering, 4,14) and chemical reduction 8,11,17,21,22) which tend to cause inhomogeneity and microsegregation.…”
Section: Introductionmentioning
confidence: 99%